2006
DOI: 10.1175/jtech1855.1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation Calibration of an X-Band Weather Radar Using a Microwave Link

Abstract: The attenuation of a radar signal is a serious problem facing meteorologists and hydrologists. In heavy rain, reflectivity information can be completely lost from large portions of a radar scan. The problem is particularly acute for X-band radars. Current methods of correcting for attenuation face many difficulties, mainly because the actual amount of attenuation at any given time is unknown. In this paper a backward-iterative attenuation-correction algorithm is presented that uses the attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Krämer et al (2005) adopted the attenuation and rainfall information derived from a microwave link with its receiver colocated with an X-band weather radar as a reference to correct the radar data for rainfall estimation [15]. Using the same link as in [15], Rahimi et al (2006) presented a backwarditerative attenuation correction algorithm on which the link attenuation constraint was imposed [16]. Trömel et al (2014) demonstrated that the ratio of / DP can be optimized with the help of microwave links oriented along radar radial [14].…”
Section: Introductionmentioning
confidence: 99%
“…Krämer et al (2005) adopted the attenuation and rainfall information derived from a microwave link with its receiver colocated with an X-band weather radar as a reference to correct the radar data for rainfall estimation [15]. Using the same link as in [15], Rahimi et al (2006) presented a backwarditerative attenuation correction algorithm on which the link attenuation constraint was imposed [16]. Trömel et al (2014) demonstrated that the ratio of / DP can be optimized with the help of microwave links oriented along radar radial [14].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of microwave attenuation can be obtained by measuring the difference between clear and rainy days, and these data can be used to retrieve rainfall intensity and its spatial distribution [9,10] and correct the radar reflectivity factor as a constraint. Krämer et al [11,12] described forward and backward iterative algorithms that can be used to correct the X-band radar reflectivity factor using a 10.5/17.5 GHz dual-frequency microwave link. Krämer and Verworn [13] used a dual-frequency microwave link to correct the C-band radar reflectivity factor.…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…The meanings of the other quantities in (12) are shown in Figure 1. Meanwhile, the Radon inverse transform satisfieŝ The corresponding tomography is the inverse of the Radon transform.…”
Section: Reconstruction Of the Grid Attenuation Using Microwavementioning
confidence: 99%
“…Kidd and Levizzani (2011) and Kidd and Huffman (2011) have summarized some of the efforts given to improve the accuracy of satellite rain-rate estimation. Several studies investigated rain-rate estimation using microwave links as another potential source of data (Overeem et al, 2013;Rahimi et al, 2006;Upton et al, 2005;Zinevich et al, 2009), where a line-averaged precipitation is estimated therefrom. Acoustic rain gauges are an economical alternative which analyze the raindrops' sound similar to when one listens to rain in a tent (de Jong, 2010).…”
Section: Introductionmentioning
confidence: 99%